Ibrutinib-associated alveolar hemorrhage and spontaneous hemothorax - Tombul, Ismail; Sayan, Muhammet; Dundar, Nazlihan; Dikyar, Asena; Yildiz, Seyma; Celik, Ali (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2022)
Ibrutinib is an irreversible inhibitor of Bruton’s tyrosine kinase (BTK), a cytoplasmic tyrosine kinase of the Tec family, which plays an important role in the B-cell receptor signaling pathway [1]. Ibrutinib is used for the treatment of chronic lymphocytic leukemia, mantle cell lymphoma, Waldenström macroglobulinemia, and graft versus host disease [2]. Ibrutinib predisposes to bleeding by inhibiting BTK and Tec, which play a role in the inhibitory signaling pathway of platelet collagen receptors such as glycoprotein VI (GP VI) and C-type lectin-like receptor 2 (CLEC-2). In addition, ibrutinib has an inhibitory effect on the interaction of von Willebrand factor and glycoprotein-1b (GP 1b), and microvascular hemorrhages can be explained by this mechanism [3]. Cases of ibrutinib-related minor bleeding besides fatal hemorrhages such as subdural hematoma, gastrointestinal bleeding, and very rarely hemothorax, have been reported in the literature [2, 4]. Here, we aimed to present a case of ibrutinib-related alveolar hemorrhage and spontaneous hemothorax in a patient with pulmonary graft versus host disease due to allogeneic stem cell transplantation performed for acute lymphoblastic leukemia.